Optimizing Selection of Sexually Mature Barbus Altianalis For Induced Spawning: Determination of Size at Sexual Maturity of Populations from Lake Edward and Upper Victoria Nile in Uganda - Aruho, Cassius; Ddungu, Richard; Nkalubo, Winnie; Ondhoro, Constantine Chobet; Bugenyi, Fredrick; Rutaisire, Justus (Fisheries and Aquatic Sciences, 2018)
Sexual maturity (L50), the length at which 50% of fish in a size class are mature, is a key aspect of domestication of new fish species because it guides the procedure for identification of appropriate broodstock size for artificial spawning. In this study, the L50 was determined for 1083 Barbus altianalis samples obtained from Lake Edward and the Upper Victoria Nile. Gonads of freshly killed samples were examined macroscopically and verified with standard histological procedures for the maturation stages that were used to determine L50. Oocytes and spermatogenic cell sizes were compared for fish obtained from both water bodies. Results indicated that there were no variations in macro gonad features observed for fish from Lake Edward and Upper Victoria Nile. Similarly, there were no significant differences in oocyte sizes (P > 0.05) between the two populations but significant differences in spermatogenic cell sizes were noted (P < 0.05) except for spermatozoa (P > 0.05). This however did not suggest peculiar differences between the two populations for staging the gonads. Consequently, no staging variations were suggested for both populations in determination of L50. Sexual maturity was found in the same class size of fork length (FL) 20–24.9 cm and 35–39.9 cm for males and females from both water bodies, respectively. At this FL, however, males were too small, and for good selection of vigor broodstocks for spawning and conservation purposes, they are better picked from class size of 30–34.9 cm FL and above. These findings were crucial for integration of appropriate breeding size in spawning protocol by farmers and fisheries scientists conserving wild B. altianalis populations.
Keywords: Sexual maturation; Staging; Oocyte sizes; Spermatozoa